THE INFLUENCE OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE (CASE STUDY) IN SEVERAL DISTRICT HEALTH CENTERS SOUTHWEST ACEH) - Hartati Astina; Likdanawati; Marbawi; Hamdiah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study was conducted to examine the Influence of Transformational and Transactional Leadership on Employee Performance Through Organizational Commitment as an Intervening Variable in Several Health Centers in Southwest Aceh Regency. This type of research uses a quantitative method, data collection using a questionnaire containing questions and statements by distributing it to the employees concerned at the Health Centers in Southwest Aceh Regency. This research was conducted at 3 Health Centers in Southwest Aceh Regency, namely Alue Sungai Pinang, Alue Pisang and Babahrot Health Centers. The population in this study were employees of the Health Centers in Southwest Aceh Regency totaling 173 employees. While the number of samples in this study was 64 employees. The data analysis method used was path analysis and was processed with the help of the Statistical Package for Social Science (SPSS) application program. The results of the study showed that there was an influence of transformational and transactional leadership on organizational commitment and there was also an influence of transformational, transactional and organizational commitment leadership on the performance of employees of the Health Centers in Southwest Aceh Regency. Furthermore, the research results found that the organizational commitment variable fully mediates (full mediation) the relationship between transformational leadership and the performance of employees at the Southwest Aceh District Health Center and the organizational commitment variable directly mediates (partial mediation) the relationship between transactional leadership and the performance of employees at the Southwest Aceh District Health Center.